Interferência das plantas daninhas na nutrição e produtividade da cultura da berinjela cultivar 'Nápoli' com e sem tutoramento e desbrota - Marques, Luiz Junior Pereira [UNESP] (2015)
The aim of this study was to identify the main weed, determine the periods of interference and the effects of weed community in the accumulation of nutrients in the eggplant crop in two driving ways: with and without staking and thinning. The studies were conducted in Jaboticabal, SP, on the campus of FCAV-UNESP in two years of cultivation. In the first year (2013), the culture was conducted without staking and thinning (STD) and in the second year (2014) with staking and thinning (CTD). Treatments consisted of 11 increasing periods of control and coexistence with weeds: (0-14, 0-28, 0-42, 0-56, 0-70, 0-84, 0-98, 0-112, 0-126, 0-140 and 0-154 DAT). Phytosociological studies and productivity were evaluated to determine the periods of interference. Two treatments were carried out to evaluated the accumulation of dry matter and macronutrients of eggplant 'Napoli' with and without presence of weeds. The main weeds responsible for interference were Eleusine indica, Nicandra physaloides, Portulaca oleracea on crops STD and CTD. The weed community reduced the eggplant fruit yield by 96% in STD and 78% in CTD cultivation. In STD cultivation, the critical period of interference (PCPI) started in the range six to fourteen DAT and finished in the range 84 to 102 DAT. In CTD cultivation PCPI starts at 29 and ends in the range 42 to 48 DAT. Weeds reduced the accumulation of nutrients in the order of 70.22 ± 6.96% in the STD farming and 67 ± 4.7% in the CTD cultivation. For dry matter accumulation was observed reductions in the order of 82.89% and 63.85% for crops STD and CTD, respectively. So that the weeds, Eleusine indica, Nicandra physaloides, Portulaca oleracea showed greater potential for interference in the periods 6-102 DAT in STD farming and 29-48 in CTD cultivation, reducing productivity, dry matter and nutrient accumulation of eggplant Napoli in percentage higher than 50%